NUMERICAL ANALYSIS IN ARTERIAL STENOSIS AFFECTED BY ISCHEMIC HEART DISEASE USING FINITE VOLUME METHOD - Fatahillah, Arif; Pratiwi, Alfiani Dyah; Setiawani, Susi; Kristiana, Arika Indah; Adawiyah, Robiatul (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Atherosclerosis is the narrowing of blood vessels caused by the buildup of cholesterol plaque on the walls of the arteries. Excessive buildup of cholesterol plaque disrupts the circulatory system, thereby affecting the speed and pressure of blood flow. In the long term, atherosclerosis can cause ischemic heart disease. This study aims to analyze the influence of stenosis, initial velocity, and diameter on the velocity and pressure of blood flow in narrowed arteries that cause ischemic heart disease. In this research, a Navier Stoke mathematical equation model was built which was solved using the finite volume method with SIMPLE discretization (Semi Implicit Method for Pressure Linked Equations). Finite volume methods are used to analyze unstructured objects such as blood flow. SIMPLE discretization is implemented simply in two and three dimensions with a system of equations containing fluid motion. Matlab and Fluent are software used for process simulations, Matlab for visualizing graphs of numerical calculation results, and Fluent for visualizing blood flow. Based on the simulation results, it can be concluded that the smaller the diameter, the greater the stenosis, and the greater the initial velocity, the greater the blood flow velocity. On the contrary, the diameter gets smaller, the stenosis gets bigger, and the initial velocity gets bigger so that the pressure on the blood flow gets smaller. Blood flow simulation has the potential to contain ischemic heart disease if the maximum speed produced is greater than the maximum normal blood speed, namely 0.45 m/s.